FUTURE DEVELOPMENT OF COHORT LIFE EXPECTANCY IN SWEDEN - Petr Mazouch (European Scientific Journal, ESJ, 2014)
The aim of the paper is to analyze future development of cohort life expectancy in Sweden. Life expectancy from cohort perspective brings different information about mortality patterns than traditional period life expectancy. Analysis show that changes in life style and different mortality patterns could cause rapidly increase of life expectancy for current cohorts. Future development is based on simple alternative approach of mortality modeling (future estimates of mortality rates) which is based on cohort mortality patterns. The assumption of constant change of the force of mortality between two following ages across cohorts is the fundamental base of the proposed model. Estimation of cohort life expectancy based on presented model for already extinct cohorts is compared with empirical life expectancy which is already known and forecasting of cohort life expectancy for still living cohorts is done.